Apreciação da fauna ictioparasitária em pesqueiro, tipo pesque-pague do município de Guariba - SP - Schalch, Sergio Henrique Canello [UNESP] (Universidade Estadual Paulista (Unesp), 2002)
This research was designed to identify the main parasite diseases in different species of fish from fee-fishing at Guariba, State of São Paulo. This country is beated at latitude: 21°15'22 S, longitude 48°18'58 W, in altitude 595 meters. The research was developmento in period april, 1997 to march to 1999, seeking to verified the caractheristics of epizootic outbreaks, the Kind tissues lesions 408 fishes were examinated during a period of one year, the datas demonstred que 29,1% of them were infsted by the protozoans e metazoans. Leporinus macrocephalus shawed the highest parasitism by Trichodina sp, although Piaractus mesopotamicus and Cyprinus carpio were also parasited. Piscinoodinium pillulare infestation were found in L. macrocephalus, P. mesopotamicus, C. carpio e Colossoma macropomum. Monogenetics metazoa have largely been observed in L. macrocephalus, P. mesopotamicus, C. carpio, C. macropomum e cross-bred tambacu, despit of their incidence that was elevated in the summer for L. macrocephalus, spring for P. mesopotamicus and C. macropomum, and both seasons for cross-bred tambacu. Lernaea cyprinacea copepodes were observed in L. macrocephalus, P. mesopotamicus, C. carpio and cross-breeding tambacu, in spite of the fact thot C. carpio has demonstred high parasitism of adult form. L. macrocephalus, P. mesopotamicus e C. carpio showed susceptibility to Dolops sp parasitism, even though the main prevalence was observed during the summer and autumn seasons. P. mesopotamicus was the most susceptibility specie to the myxosporídeos, however this parasite were also identified in L. macrocephalus and cross-breeding tambacu. Severe gill lesions have been observed in L. macrocephalus e P. mesopotamicus caused by monogenetics, P. pillulare e Trichodina sp parasitism, such as: extensive hemorrhage area, sub epithelium edema, the primary and secondary lamina was hiperplastic, fusion of ...

Este trabalho contribui para o conhecimento das principais espécies de parasitos causadores de danos aos peixes de pesqueiros comerciais do tipo pesque-pague em Guariba. Este município está localizado a 21°15'22Latitude S e 48°18'58 Longitude W, com altitude de 595metros. As pesquisas foram desenvolvidas no período de abril de 1997 a março de 1999, visando determinar quais as características de eventuais surtos epizoóticos, o tipo de resposta tecidual provocada nos hopspedeiros e qual a melhor forma de controle do parasitismo. Dos 408 peixes examinados, 29,1% estavam parasitados pelos protozoários Trichodina sp e Piscinoodinium pillulare e pelos metazoários helmintos monogenóides, Lernaea cyprinacea, copepoditos de Lernaea cyprinacea, Dolops sp e myxosporídeos. O Leporinus. macrocephalus foi a espécie que apresentou os maiores índices de parasitismo por Trichodina sp, seguido de Piaractus mesopotamicus e Cyprinus carpio. Este parasito não foi assinalado no tambacu, Brycon cephalus, Brycon hillarii e Colossoma macropomum. O L. macrocephalus, P. mesopotamicus, C. carpio e C. macropomum foram intensamente parasitados pelo P. pillulare, mas no tambacu a infestação foi baixa. Estes protozoários infestaram L. macrocephalus na primavera e verão. Os helmintos monogenóides infectaram intensamente L. macrocephalus, P. mesopotamicus, C. carpio, C. macropomum e tambacu, não sendo diagnosticado em B. cephalus e B. hillarii. Em L. macrocephalus a ocorrência de helmintos monogenóides foi maior no verão; em P. mesopotamicus na primavera; no tambacu na primavera e verão e em C. macropomum a maioria das ocorrências foram assinaladas na primavera. Os Copepoditos de L. cyprinacea foram observados em L. macrocephalus, P. mesopotamicus, C. carpio e tambacu. Porém, C. carpio foi a espécie mais parasitada por L. cyprinacea adulto. Houve alterações sazonais estatisticamente...
Keywords: Peixe - Parasito; Histopatologia; Fauna de rio; Epidemiologia; Parasitismo; Fishes